(untitled) (Studia austriaca, 2023)
Even though Robert Menasse claims, through the words of his alter ego Roman Gilanian, the protagonist of Sinnliche Gewissheit [Sensual Certainty], that he does not know what to say about the Brazilians, this novel displays a certain portrait of Brazil. As a land of blatant social injustice, of sensuality, hedonism and irrationality, Brazil is at the same time fascinating and repulsive for a novelist who sees it through European eyes. For Menasse, Brazil remains foreign and mysterious, a land full of contradictions and paradoxes that seem to pose a threat to his philosophical concepts. This article highlights three themes that play a key role in the plot of Sinnliche Gewissheit: colonialism, regression and sensuality which, at the same time, challenge the idea of Heimat.